Longitudinal associations between executive control and body mass index across childhood. Issue 4 (2nd November 2021) - Tomaso, Cara C.; James, Tiffany; Nelson, Jennifer M.; Espy, Kimberly A.; Nelson, Timothy D.
Summary: Background: Childhood obesity remains a prevalent public health concern. Executive control, a set of higher‐order cognitive abilities for directing attention and behaviour, has been identified as a malleable factor potentially related to weight outcomes in youth. However, the directionality of this relationship remains unclear. Objectives: This study examined reciprocal associations between three executive control components—inhibitory control, working memory and flexible shifting—and BMI (body mass index) percentile during childhood. Methods: At four points throughout elementary school, a community sample ( N = 294) completed executive control tasks and had their height and weight objectively measured. Controlling for sex and socioeconomic risk status, random intercept cross‐lagged panel models were tested. Results: Better inhibitory control performance predicted lower subsequent BMI at each timepoint, and better working memory and flexible shifting performance in grade three both predicted lower subsequent BMI in grade 4. However, BMI did not predict subsequent executive control performance at any timepoint. Conclusions: Executive control abilities, including automatic response modulation, being able to hold and manipulate mental information, and being able to make flexible mental transitions, may be protective against weight problems, particularly in middle childhood when these abilities have had more time to mature and children begin to gain more independence.